2022
DOI: 10.1108/jhtt-05-2021-0143
|View full text |Cite
|
Sign up to set email alerts
|

What people TikTok (Douyin) about influencer-endorsed short videos on wine? An exploration of gender and generational differences

Abstract: Purpose This study aims to understand social media users’ responses to the influencer-endorsed wine short videos on the most popular platform – Douyin, relying on message interpretation process (MIP) framework and identify segmentation differences from gender and the generational cohorts (Gen Z and Gen Y). Design/methodology/approach Topic modeling, content analysis and quantitative analysis were used to decipher the user-generated content (UGC) data retrieved from 81 wine videos posted by the top 30 social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Communication today cannot ignore the significant changes that have occurred in recent years in the ways and means utilized by companies for communication purposes. It would therefore be interesting to consider the importance of social networks and the emergence of prominent figures such as social influencers [81,82]. In fact, considering the increasing importance of wine influencers in the wine sector, the use of wine influencers could help to "tell the story" of the wine effectively, through storytelling (communicating their personal experiences using videos and images), providing information generated by the influencer himself/herself, and the additional interaction between the followers [10,63].…”
Section: Discussionmentioning
confidence: 99%
“…Communication today cannot ignore the significant changes that have occurred in recent years in the ways and means utilized by companies for communication purposes. It would therefore be interesting to consider the importance of social networks and the emergence of prominent figures such as social influencers [81,82]. In fact, considering the increasing importance of wine influencers in the wine sector, the use of wine influencers could help to "tell the story" of the wine effectively, through storytelling (communicating their personal experiences using videos and images), providing information generated by the influencer himself/herself, and the additional interaction between the followers [10,63].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the second research question, the results discovered that attachment to social media influencer significantly mediates destination authenticity and enjoyment. A possible explanation is that the participants in the current study are predominantly millennial consumers who have a wide range of enthusiasm and engagement with social media influencers (Deng et al , 2022). Thus, this helps us understand why attachment to social media influencer has a significant mediating effect on social media experience.…”
Section: Discussionmentioning
confidence: 86%
“…For instance, through the UGC platform, destination marketers can upload videos featuring influencers to showcase destination scenery (Yen et al , 2019). This influencer marketing method has increasingly garnered the interest of academics (Geng et al , 2020; Jin and Ryu, 2020; Deng et al , 2022). Although some research indicated that social media influencers are a problematic group in China, with some of them having both positive (e.g.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After motivation and trigger are both secured, Douyin continues to drive the consumers to feel that they have the ability to take an action. Douyin provides short videos that last for only around fifteen seconds to ten minutes [9]. Therefore, users can take a low extra cost to make videos on Douyin since it only requires one mobile device and can be accessed in any external environment as long as the internet is available.…”
Section: The Hook Modelmentioning
confidence: 99%